Responses of transcriptome and metabolome in peanut leaves to dibutyl phthalate during whole growth period - Fan, Lixia; Zhang, Bingchun; Ning, Mingxiao; Quan, Shuangjun; Guo, Changying; Cui, Kai; Chen, Lu; Yan, Mengmeng; Ren, Xianfeng (Frontiers in Plant Science, 2024)
The application of agricultural film mulching technology has significantly contributed to increasing crop yield and income, but the pollution caused by residual film has seriously affected agricultural production and the natural environment. Agricultural film is commonly employed to enhance the yield of peanuts; its use may lead to excessive dibutyl phthalate (DBP) residues in peanut kernels. But, limited investigations have been conducted on the regulatory mechanism of peanut leaves in response to DBP exposure throughout the entire growth period. To bridge this knowledge gap, we investigated the differences in transcriptome and metabolome of peanut leaves under DBP stress. According to visual observations, the results of morphological response showed that the growth of peanut plants was significantly inhibited from seedling to pod stage under DBP treatment. Transcriptomic analysis results showed that the genes AH19G05510 (LRR receptor-like serine threonine-protein kinase) and AH20G31870 (disease resistance), belonging to the FAR1 family and bZIP family respectively, may be key genes involved in the resistance to DBP stress throughout its growth stages. Metabolomic analysis results showed that during the initial stage of DBP stress, the key metabolites in peanut leaves response to stress were carboxylic acids and derivatives, as well as fatty acyls. As peanut growth progressed, flavonoids gradually became more prominent in the resistance to DBP stress. By integrating metabolomics and transcriptomics analysis, we have identified that purine metabolism during seedling and flowering stages, as well as the flavone and flavonol biosynthesis pathways during pod and maturity stages, played a crucial role in response to DBP stress. These findings not only provide valuable key gene and metabolic information for studing anti-plasticizer pollution throughout the entire growth period of peanuts, but also offer reference for enhancing crop resistance to plasticizer pollution through genetic modification and metabolic regulation.